CEBP factors regulate telomerase reverse transcriptase promoter activity in whey acidic protein‐T mice during mammary carcinogenesis. Issue 9 (25th October 2012) - Kumar, Mukesh; Witt, Britta; Knippschild, Uwe; Koch, Sylvia; Meena, Jitendra K.; Heinlein, Christina; Weise, Julia M.; Krepulat, Frauke; Kuchenbauer, Florian; Iben, Sebastian; Rudolph, Karl‐Lenhard; Deppert, Wolfgang; et al.
Abstract Telomerase is activated in the majority of invasive breast cancers, but the time point of telomerase activation during mammary carcinogenesis is not clear. We have recently presented a transgenic mouse model to study human telomerase reverse transcriptase (TERT) gene expression in vivo (hTERTp‐lacZ). In the present study, hTERTp‐lacZxWAP‐T bitransgenic mice were generated to analyze the mechanisms responsible for human and mouse TERT upregulation during tumor progression in vivo. We found that telomerase activity and TERT expression were consistently upregulated in SV40‐induced invasive mammary tumors compared to normal and hyperplastic tissues and ductal carcinoma in situ (DCIS). Human and mouse TERT genes are regulated similarly in the breast tissue, involving the CEBP transcription factors. Loss of CEBP‐α and induction of CEBP‐β expression correlated well with the activation of TERT expression in mouse mammary tumors. Transfection of CEBP‐α into human or murine cells resulted in TERT repression, whereas knockdown of CEBP‐α in primary human mammary epithelial cells resulted in reactivation of endogenous TERT expression and telomerase activity. Conversely, ectopic expression of CEBP‐β activated endogenous TERT gene expression. Moreover, ChIP and EMSA experiments revealed binding of CEBP‐α and CEBP‐β to human TERT‐promoter. This is the first evidence indicating that CEBP‐α and CEBP‐β are involved in TERT gene regulation during carcinogenesis.